Telephone health survey estimates: Effects of nonresponse and sample limitations. (18th January 2019) - Fowler, Floyd J.; Brenner, Philip S.; Buskirk, Trent D.; Roman, Anthony
Abstract : Objective: The objective of this study was to assess nonresponse error in telephone health survey data based on an address‐based sample. Data Sources: Telephone and in‐person interviews in Greater Boston. Study Design/Data Collection: Interviewers attempted telephone interviews at addresses that were matched to telephone numbers using questions drawn from federal health surveys. In‐person household interviews were carried out with telephone nonrespondents and at addresses without matching telephone numbers. Principal Findings: After adjusting for demographic differences, only eight of 15 estimates based on the telephone interviews lay within two standard errors of the estimates when data from all three groups were included. Conclusions: For health surveys of address‐based samples, many estimates based on telephone respondents differ from the total population in ways that cannot be corrected with simple demographic adjustments.